2014
DOI: 10.1007/s00277-014-2108-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary prophylaxis of invasive fungal infections in patients with haematologic malignancies. 2014 update of the recommendations of the Infectious Diseases Working Party of the German Society for Haematology and Oncology

Abstract: Invasive fungal infections cause substantial morbidity and mortality in immunocompromised patients, particularly in those with haematological malignancies and recipients of allogeneic haematopoietic stem cell transplantation. Difficulties in diagnosing invasive fungal infections and subsequent delays in treatment initiation lead to unfavourable outcomes and emphasise the importance of prophylaxis. Since the recommendations of the Infectious Diseases Working Party of the German Society for Haematology and Oncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 37 publications
1
72
1
5
Order By: Relevance
“…Almost all transplant recipients received antifungal agents at more than the minimum dose recommended for prophylaxis according to current treatment guidelines (11,12). The incidence of BC in our study was predicted to be higher than that among allo-HSCT recipients found in previous studies (14,15).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Almost all transplant recipients received antifungal agents at more than the minimum dose recommended for prophylaxis according to current treatment guidelines (11,12). The incidence of BC in our study was predicted to be higher than that among allo-HSCT recipients found in previous studies (14,15).…”
Section: Discussioncontrasting
confidence: 55%
“…In the present study, all 17 recipients who developed BC during micafungin adminis- tration received 150 mg/day micafungin. In general, in current treatment guidelines, a lower dose of micafungin (50 mg/day) has been approved for use for prophylactic administration (11,12). This is probably why there are only a few studies on the development of BC when a sufficient dose of micafungin (Ն100 mg/day) is provided (9,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fungal and Viral Oral Infections in individuals with Onco-Hematologic Neoplasms in a University Hospital Fungal and Viral Oral Infections in individuals with Onco-Hematologic Neoplasms in a University Hospital the author affirmed that the patients were in an advanced stage of the disease, with inadequate nutritional and oral hygiene status, whereas in the present study, the patients were on nutritional support therapy, antifungal prophylaxis with a systemic antifungal agent 22 , received oral hygiene instructions and underwent dental follow-up during antineoplastic therapy, therefore presenting adequate oral hygiene.…”
Section: Discussionmentioning
confidence: 57%